Psychosocial aspects and temporomandibular disorders in dental students - Melo Rocha, Cibele Oliveira de [UNESP]; Peixoto, Raniel Fernandes; Bastos Machado de Resende, Camila Maria; Medeiros Alves, Arthur Cesar de; Roncalli da Costa Oliveira, Angelo Giuseppe; Seabra Barbosa, Gustavo Augusto (Quintessence Publishing Co Inc, 2017)
Objective: Dental students have high levels of anxiety that can affect not only academic performance but also increase the risk for other diseases. It is believed that the increase in the incidence of chronic orofacial pain in temporomandibular disorders (TMDs) may have an impact on the quality of life and general health of subjects. The aim of this study was to evaluate the prevalence of TMD in dental students and its association with general health, quality of life, and anxiety. Method and Materials: Ninety students were evaluated by four questionnaires to determine the prevalence and sever ity of TMD (Fonseca's questionnaire) and to quantify general health (General Health Questionnaire - GHQ), quality of life (World Health Organization Quality of Life - Brief version - WHOQOL-brief) and anxiety levels (State - Trait Anxiety Index - STAI). Results: Approximately 58.9% of dental students presented TMD. Among the indicators of general health, psychologic stress (P =.010), distrust in their own performance (P =.012), and psychosomatic disorders (P =.020) showed a statistically significant difference with the presence of TMD. The four areas proposed in the questionnaire regarding quality of life, such as physical (P =.016), psychologic (P <.001), social (P =.045), and environmental (P =.017) factors also showed significant differences with the presence of TMD. Conclusion: A high prevalence of TMD was observed in dental students. In addition, some psychologic domains are important psychosocial indicators associated with the presence of TMDs.
Keywords: anxiety; epidemiology; general health; quality of life; temporomandibular joint disorders